Design and test of operation parameters for rice air broadcasting by unmanned aerial vehicle - Jiyu, Li; Yubin, Lan; Zhiyan, Zhou; Shan, Zeng; Cong, Huang; Weixiang, Yao; Yang, Zhang; Qiuyang, Zhu (International Journal of Agricultural and Biological Engineering, 2016)
Considering the difficulty of broadcasting in the small plots and complex terrain in South China, this research aimed to explore a new efficient broadcasting way and figure out advisable operation parameters by using a hollow 12-axis, rotor-wing Unmanned Aerial Vehicle (UAV) which is typically made up of four groups of solid support structure, with each consisting of three axes and two rotor wings. A 3.7 L reverse pyramid-shape seed hopper with a 60 mm×13 mm rectangular outlet at the bottom was designed to realize self-gravity seeding. Rice seed firstly directly falls on the rotating disc driven by direct-current dynamo before being sown. The disc was located 120 mm above the ground, with a diameter of 350 mm. Under constant flight conditions, parameters of the on-board broadcasting devices (dropping speed referring to speed for the outlet and the broadcasting speed for the disc’s rotation speed) determine the uniformity of air broadcasting. The FUTABA T8FG transmitter and receiver system were employed as the remote control device. When the UAV flies at 3 m/s and 2 m above the ground with an expected seeding of 180 grain/m2, the RD (Right Down) knob marked 29 and LD (Left Down) knob marked -24 with a disc rotation speed of 900 r/min, the broadcasting lasts for 15 seconds with a 25% opening (1.95 cm2) of rectangular outlet. In order to verify the feasibility of air broadcasting parameters, the project team carried out a field broadcasting test by using a hollow multi-rotor UAV at Zhongluotan Test Base in Guangzhou in July, 2014. In the square field plots of 0.09 hm2, flying path of air broadcasting operation was designed. The collected sampling data of broadcasting quantity per unit area after the test showed that there were, on average, 187.4 grains/m2 of the five sampling points with a standard deviation of 22.77, and a coefficient of variation of 12.15% which was far smaller than that of artificial broadcasting. The average yield of field broadcasted by UAV is 7705.5 kg/hm2 in 2014, implying that rice air broadcasting by UAV is feasible. Keywords: air broadcasting, test, 12-axis UAV, , self-gravity seeding, operation parameters, yield, rice DOI: 10.3965/j.ijabe.20160905.2248 Citation: Li J Y, Lan Y B, Zhou Z Y, Zeng S, Huang C, Yao W X, et al. Design and test of operation parameters for rice air broadcasting by unmanned aerial vehicle. Int J Agric & Biol Eng, 2016; 9(5): 24－32.